Challenges experienced by induced lactation women in Malaysia: An exploratory qualitative study. - Norsyamlina Che Abdul Rahim; Zaharah Sulaiman; Tengku Alina Tengku Ismail (PLoS ONE, 2024)
Background Induction of lactation occurs when breast milk is produced in a human (woman), without going through the process of pregnancy and delivery. Efforts to produce milk by women who had never been pregnant and give birth are not easy. According to the many who have attempted it, it is far more arduous a task than initiating postpartum lactation, but it is possible and worth the effort. Research aim This study aimed to explore and understand the challenges for women during induced lactation in Malaysia. Methods This qualitative study was done in 2017 and utilized in-depth interview among women who induced lactation in five states based on five regions in Malaysia [Central Region (Selangor), Northern Region (Penang), Southern Region (Johor), East Coast Region (Kelantan), Malaysia Borneo (Sabah)]. All interviews were consented, audio-recorded then transcribed verbatim, followed by identification of main themes. Results Data saturation was achieved after interviewing a total of 23 induced lactation women. Data synthesized using thematic analysis revealed six themes describing the main challenges during the induction process were (1) health condition, (2) work commitment, (3) overexertion, (4) not eligible to take leave, (5) inability to follow the treatment plan, and (6) difficulty attaching the adopted baby to initiate breastfeeding during induced lactation process. Conclusions The challenges faced by women during the process of induced lactation were complex and the induced lactation process requires considerable dedication and determination. The findings of this research will help other women and their spouses/partners comprehend the challenges, obstacles, and support that are needed along the induced lactation process. The Government and other stakeholders have roles in more efforts and programs to help these mothers breastfeed their adoptive child and make them feel more accomplished as women and mothers.